Characteristics of changes in retinal and optic nerve microvascularisature in Leber hereditary optic neuropathy patients seen with optical coherence tomography angiography - Sheremet, N L; Shmelkova, M S; Andreeva, N A; Zhorzholadze, N V; Fomin, A V; Krylova, T D; Tsygankova, P G (Vestnik oftal'mologii, 2020)
To investigate the features of various parameters of the density of retinal blood vessels, optic nerve head (ONH) and peripapillary region in hereditary optic neuropathy (HON) patients revealed with optical coherence tomography angiography (OCTA).PURPOSETo investigate the features of various parameters of the density of retinal blood vessels, optic nerve head (ONH) and peripapillary region in hereditary optic neuropathy (HON) patients revealed with optical coherence tomography angiography (OCTA).The study included 29 HON patients divided into three groups based on symptoms duration (less than 1 year; 1-5 years, more than 5 years) and visual acuity (0.5-1.0; 0.04-0.4; 0.03 and lower). Relative macular, optic disc and peripapillary vessel density (VD, %) was assessed by OCTA (xR Avanti, Optovue Inc., USA).MATERIAL AND METHODSThe study included 29 HON patients divided into three groups based on symptoms duration (less than 1 year; 1-5 years, more than 5 years) and visual acuity (0.5-1.0; 0.04-0.4; 0.03 and lower). Relative macular, optic disc and peripapillary vessel density (VD, %) was assessed by OCTA (xR Avanti, Optovue Inc., USA).Significant progressive VD reduction in superficial capillary plexus (SCP) was detected in all parafovea sectors and in the temporal sector of perifovea over the course of disease progression. No significant differences of these parameters were found in correlation with visual acuity. Patients with VA of 0.5-1.0 turned out to have greater VD in deep capillary plexus (DCP), whereas no differences were found in relation to the duration of HON. A strong significant correlation between the SCP and DCP VD only in central foveal area was revealed in all groups depending on the VA and symptoms duration. Over the course of HON progression, VD in the temporal sector and in temporal segments of superior and inferior sectors has gradually reduced. In patients with VA of 0.5-1.0, the retinal nerve fibers layer (RNFL) thickness in the temporal sector and optic nerve VD was notably greater compared to patients with lower VA. The most significant correlation was established between VA and structural changes (K=0.75, p<0.001) and VD in the temporal sector (K=0.57-0.61, p<0.001).RESULTSSignificant progressive VD reduction in superficial capillary plexus (SCP) was detected in all parafovea sectors and in the temporal sector of perifovea over the course of disease progression. No significant differences of these parameters were found in correlation with visual acuity. Patients with VA of 0.5-1.0 turned out to have greater VD in deep capillary plexus (DCP), whereas no differences were found in relation to the duration of HON. A strong significant correlation between the SCP and DCP VD only in central foveal area was revealed in all groups depending on the VA and symptoms duration. Over the course of HON progression, VD in the temporal sector and in temporal segments of superior and inferior sectors has gradually reduced. In patients with VA of 0.5-1.0, the retinal nerve fibers layer (RNFL) thickness in the temporal sector and optic nerve VD was notably greater compared to patients with lower VA. The most significant correlation was established between VA and structural changes (K=0.75, p<0.001) and VD in the temporal sector (K=0.57-0.61, p<0.001).The obtained data suggest that derivative microvascular changes play an active role in the clinical progression of the disease.CONCLUSIONThe obtained data suggest that derivative microvascular changes play an active role in the clinical progression of the disease.